A study on the microstructures and three–body abrasive wear behaviors of Fe–B alloy under different Fe2B boride orientation. Issue 5 (4th September 2017) - Yi, Dawei; Zhang, Zhiyun; Chen, Jin; Niu, Libin; Peng, Jianhong
Abstract : Purpose: The directional solidification Fe-B alloy was prepared. The microstructures and three-body abrasive wear behaviors of directional solidification alloy were investigated. Design/methodology/approach: Fe-B alloy was melted in medium frequency induction furnace. The hardness was measured on HRS-150 Rockwell-hardness tester and HXD-1000TMC tester. The wear characteristic of the alloy was examined with a block-on-ring geometry. The worn surface of the alloy was investigated by scanning electron microscopy and laser scanning microscopy. Findings: The wear weight loss and worn surface roughness increase with the increasing contact load in wear tests. When the worn surface is perpendicular to the boride growth direction, the highest hardness plane of the boride can resist abrasive effectively under the surrounding and supporting of the martensite matrix. Originality/value: The relation between boride growth direction and wear direction will cause different boride breaking tendency and wear weight loss.